Practical reliability data analysis for non-reliability engineers - Brooker, Darcy; Gerrand, Mark (Artech House, 2021)
"This resource presents basic probabilistic and statistical methods or tools used to extract the information from reliability data to make sound decisions. It consolidates and condenses the reliability data analysis methods most often used in everyday practice into an easy-to-follow guide, while also providing a solid foundation from which to explore more complex methods if desired"-- Source other than Library of Congress.
Keywords: Reliability (Engineering) -- Statistical methods.; elektronické knihy; electronic books